Partisipasi Masyarakat Sipil dalam Otonomi Daerah Menurut Undang-Undang No. 22 Tahun 1999 - Mustari Pide (Jurnal Hukum IUS QUIA IUSTUM, 2000)
The 1999 Regulation Number 22 gives awide opportunity for the local people to participate in the government and development. To make the efforts grow, develop and well adopted the civil society existence is need to articulate them. It could articulate the people interest if it solid a support from the local government and local people.